The role of work nursing in the prevention of the risks of workers exposed to pesticides: a bibliographical review (Research, Society and Development, 2019)
The objective of the study is to establish the main aspects of workers' exposure to chemical agents and to define the relationship with the risks capable of making their health and quality of life unstable. This is an integrative review of the literature, in which the studies and works made available on the SCIELO and Google Scholar platform were compiled and analyzed theoretically. As a result, the nursing actions of the work in the awareness of the participating agents, the strategic degree actions to maintain the psychological and physical conditions, the effective participation of the states and organs in the formulation of preventive proposals, the relevance of protective equipment aiming at the elimination of risks and enhancing the personal safety of the worker, are strong and positive points for the prevention of risk to workers. The involvement of nursing professionals in the construction and implementation of actions and programs needs to be stimulated, emphasizing systematic efforts in the area of health, especially in primary health care.